An Investigation On The Enhanced Oil Recovery Performance Of Local Biopolymers - Chukwuebuka Dike; Nkemakolam Izuwa; Anthony Kerunwa; Onyebuchi Nwanwe; Nzenwa Enyioko; Boniface Obah (Journal of Chemical and Petroleum Engineering)
The introduction of polymers into the reservoir yields favorable mobility ratio between the entrapped crude and injected water to improve sweep efficiency and incremental recovery of the reservoir. Xanthan Gum is the most widely utilized bio-polymer for chemical enhanced oil recovery (CEOR), but the polymer is imported. However, recent studies have shown the potentials of local bio-polymers in alternating conventional polymer in CEOR. This have attracted serious interest due to their availability, low cost and eco-friendly nature. In this paper a comparative CEOR investigation was conducted between conventional and local polymers. Cook Pine Exudate (CPEG), Afzelia Africana (AA) and Terminalia Mantaly Exudate (TMEG) were used as local-polymer while Xanthan Gum (XG) was used conventional polymer. FTIR evaluation, aqueous stability, Viscosity, Adsorption and EOR core-flood study were conducted on the investigation. From the FTIR evaluation CPEG, AA and TMEG can be classified as polysaccharides. From Aqueous Stability test, CPEG, AA and TMEG formed colloidal phase with water. From the viscosity result CPEG, AA and TMEG recorded similar viscosity trend present in XG. From the Adsorption test, increase in concentration increased adsorption rate. From the CEOR study, favorable mobility ratio was achieved at 0.25wt% concentration for all polymers utilized for the study. 0.25wt% CPEG yielded the best recovery of the polymer formulation as it recorded additional 17.65% after secondary recovery, while TMEG, XG and AA recorded additional 16.67% 15% and 14.5% respectively. The study showed that CPEG, AA and TMEG can be used as alternative to XG